Process optimisation of selective laser melting using energy density model for nickel based superalloys. Issue 7 (2nd May 2016) - Carter, L. N.; Wang, X.; Read, N.; Khan, R.; Aristizabal, M.; Essa, K.; Attallah, M. M.
Abstract : The main challenge associated with the application of selective laser melting (SLM) to Ni based superalloys is the performance of process optimisation to maximise the mechanical properties. The energy density parameter has typically been used as a semiquantitative approach to identify the energy threshold beyond which the material achieves virtually full consolidation. Nonetheless, some Ni superalloys are susceptible to crack formation during SLM, which cannot be avoided via process optimisation. In the present report, a comparative study is presented showing the utility of the energy density parameter in process optimisation for γ′ and γ′/γ″ strengthened Ni based superalloys. For both classes, it was found that the build density increases [i.e. void area (%) decreases] with the increase in the energy density. Nonetheless, no direct correlation can be found between the energy density parameter and the cracking density.